[18F]FDG-PET/CT in different COVID-19 phases. (2020) - Ajuria-Illarramendi, Odile; Martinez-Lorca, Alberto; Orduña-Diez, Maria del Prado
Abstract: PET/CT is an hybrid technique which allows both morfological and metabolical evalutaion. Three different morphometeabolical patterns are presented which reflect the evolutive phases of the COVID-19. This findings may help the clinician determine the correct treatment and security measure that need to be taken aaccording to the phase of the disease.